Evaluation of Tahfizh Program Taajul Waqoor Li Tahfiizhil Qur’anil Kariim at an Islamic Boarding School in Bekasi - Hermanto Hermanto; Pauzan Haryono; Ibnu Muthi; Sugiyanti Sugiyanti (STAI Hubbulwathan Duri, 2022)
This research is evaluation research using the CIPP (Context, Input, Process, Product) model developed by Stufflebeam. Data was collected using interviews, observations and document studies, while the analysis was carried out using the Milles and Huberman model. This study aimed to evaluate the running of the Tahfizh Taajul Waqoor Li Tahfiizhil Qur'anil Kariim Program at an Islamic Boarding School in Bekasi. From the results of the evaluation, it is informed that the formulation of the vision, mission and objectives of the program is in a good category, only in the formulation of the vision there is one criterion that has not been met, namely vision is not static. From the input component, the input of teachers, students, curriculum and facilities and infrastructure is in a good category, only for student input that still does not meet the ideal criteria for memorizing the Qur'an. The input of the Tahfizh study room facilities in some rooms is comfortable, but there is still a need for a review of the Qur'an laboratory facilities. From the process, the use of Tahfizh's methods, media, materials and learning time is in a good category. For materials, the determination or selection of materials and targets for tahfizh is still the same in general between students with upper-middle abilities and students with low abilities. Lastly, the product components are also in a good category. To conclude, this program has already been good enough to carry on.